Neurofibromatosis Type 1 Molecular and Cellular Biology - Upadhyaya, Meena; Cooper, David N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Neurofibromatosis type 1 (NF1), caused by mutational inactivation of the NF1 tumour suppressor gene, is one of the most common dominantly inherited human disorders, affecting 1 in 3000 individuals worldwide. This book presents in concise fashion, but as comprehensively as possible, our current state of knowledge on the molecular genetics, molecular biology and cellular biology of this tumour predisposition syndrome. Written by internationally recognized experts in the field, the 44 chapters that constitute this edited volume provide the reader with a broad overview of the clinical features of the disease, the structure and expression of the NF1 gene, its germ line and somatic mutational spectra and genotype-phenotype relationships, the structure and function of its protein product (neurofibromin), NF1 modifying loci, the molecular pathology of NF1-associated tumours, animal models of the disease, psycho-social aspects and future prospects for therapeutic treatment. Neurofibromatosis Type 1: Molecular and Cellular Biology will be of great value to medical geneticists, molecular and cellular biologists, oncologists, dermatologists, neurologists, genetic counsellors and general practitioners alike.  .
From the Contents: von Recklinghausen disease -- Clinical diagnosis and atypical cases -- Management and treatment of NF1: complex UK NF1 clinics -- Mortality in NF1 -- The cognitive profile of NF1 children, therapeutic implications -- Clinical expression of NF1 in monozygotic twins -- Whole body MRI studies in NF1 patients -- Quality of Life in NF1 -- NF1 gene: promoter, 3’UTR and complex features -- Germline mutational spectrum of  NF1 and Genotype-Phenotype Correlations -- Splicing mechanisms and mutations in the NF1 gene -- NF1 Germline and somatic mosaicism -- Deep intronic NF1 mutations and possible therapeutic interventions -- NF1 microdeletions and mutational mechanisms -- NF1 somatic mutational spectrum -- Social Stigma in NF1 -- Personalized Medicine in NF1 -- Future Directions - Where do we go from here.
Keywords: Human genetics; Cancer research; Oncology .; Molecular biology; Neurosciences; Human Genetics; Cancer Research; Oncology; Molecular Medicine; Neurosciences